Evaluasi Pelaksanaan Pendidikan dan Pelatihan Teknis Kompetensi Pengelolaan Perkantoran Berbasis Teknologi Informasi (TI) Angkatan II Tahun 2014 Pada Badan Pendidikan dan Pelatihan Provinsi Jawa Tengah - Hapsari, Putri Ratna; Marom, Aufarul (Journal of Public Policy and Management Review, 2017)
This study is structured to evaluate the implementation of technical training competency office management based ini information technology class II in 2014 at the Board of Education and Training of Central Java province using indicators of success, education and training, as well as the factors that influence the success of education and training. Qualitative descriptive study with data collection through interviews, observation, documentation, and literature study. Source of information is head of the technical areas, technical training field staff on the Board of Education and Training of Central Java Province, and alumni of training participants. The study used indicator of the successfull training of Michael Hariss. Indicators participants' reactions have not been good, less active and not enthusiastic follow the training. Changes in behavior has not been good, most participants still have the same pattern of work as it did before the training. Tangible results have not been good, there are still a lot of training participants who do not apply the knowledge gained on the job because it is not related with their field. Researchers also evaluated the factors that affect the success of the training from some experts. Training participants are not good, they are less enthusiastic participants and many of them who are join the training not match with the IT field or PDE. Coach is pretty good, the ability to transfer knowledge is good but there are lack practice for the participants. Materials provided has not been good, the participants felt the training was too theoretical and less practice which are related with IT. Good facilities and infrastructure, and wireless audio wasteful battery consumption, wifi unstable, as well as computer provided insufficient number for training participants. Time management isn't good, trainers and participants alike are still frequently late for training. Based on the results of this study we can conclude that the implementation of technical training competency office management based on information technology (IT) class II in 2014 at the Board of Education and Training of Central Java province has not been good. The recommendation given that need a selection for the participants to join to make the training usefull and on target. Need to complete the infrastructure to support the learning process and provide a firm training sanctions for both trainers and participants who are indicipliner.